Pharmaceutical Standardization of Amritamanjari Rasa Prepared with Two Different Purification Media of Hingula - Bhutia, Subrat Kumar; Bramhankar, Rakesh; Das, Arun Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is one of the traditional systems of medicine. A number of medicinal preparations are developed to maintain the health and curing ailments by maintaining the balance state of Doshas and Dhatus. It is possible by Ousadhi Kalpana having herbal, animal, and metalo-mineral origin. Rasa Aushadhis are unique formulations mainly from metals and minerals and having the qualities of small dose, quick action, palatability, and longer shelf life. Amritamanjari Rasa is mentioned in Bhaishajya Ratnawali, 5th chapter, Jwara Chikitsa Prakaranam, which is best indicated in Jwara roga (Sadyojwara). Amritamanjari Rasa contains Suddha Hingula (Cinnabar), Suddha Vatsanabha (Aconitum ferox), Suddha Tankana (Borax), Pippali (Piper longum), Maricha (Piper nigrum), and Jatikosa (Jatiphala - Myirstica fragrans). The pharmaceutical procedures adopted in this study are Shodhana, Churna Nirmana, and preparation of Vati of Amritamanjari. In this study, importance is given to standardize hingula with two purificatory media i.e jambhira nimbu swarasa having strong acidic in nature and Meshi dugdha(sheep milk) having alkaline in nature. Ayurveda provides quality life to the human beings by giving emphasis on the preventive aspect of the diseases. The individuals of the later part of the 21st century are not so sound in their physical or mental health due to different adversities of life. Naturally, this physical and mental imbalance reflects in the form of various anomalies pertaining to the human body. Jwara or Fever is one of them. Fever is described as a separate illness, a symptom, and a complication of many ailments in Ayurveda classics. Despite the advancement of contemporary science, fever remains the first and foremost symptom of almost all clinical consultations. In Ayurvedic Shastras, Jwara is considered as the “king of all the diseases.” Here, living beings not only suffer physically but also mentally causing stress, worry, and anxiety.[1] It affects at any point of time throughout the life time, from birth to death.